2007
DOI: 10.1111/j.1567-1364.2006.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular glycosylphosphatidylinositol-anchored mannoproteins and proteases ofCryptococcus neoformans

Abstract: Extracellular proteins of Cryptococcus neoformans are involved in the pathogenesis of cryptococcosis, and some are immunoreactive antigens that may potentially serve as candidates for vaccine development. To further study the extracellular proteome of the human fungal pathogen Cry. neoformans, we conducted a proteomic analysis of secreted and cell wall-bound proteins with an acapsular strain of Cry. neoformans. Proteins were identified from both intact cells and cell walls. In both cases, extracellular protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
66
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 48 publications
3
66
2
Order By: Relevance
“…Furthermore, ␤-1,3 glucanase activity has been detected in cryptococcal secretions (34), and four putative endo-␤-1,3 glucanase genes are present in the cryptococcal genome data base (35). The product of one gene (CNBC2400), is present in cryptococcal cell walls (36), and the remaining three are predicted to be GPI-anchored (35). Interestingly, no ␤-1,6 glucanase genes or activity have been found, suggesting that Plb1 is linked via ␤-1,6-linked glucan to ␤-1,3-linked glucan in the central scaffold of the cell wall and that endogenous ␤-1,3 glucanases are responsible for its secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ␤-1,3 glucanase activity has been detected in cryptococcal secretions (34), and four putative endo-␤-1,3 glucanase genes are present in the cryptococcal genome data base (35). The product of one gene (CNBC2400), is present in cryptococcal cell walls (36), and the remaining three are predicted to be GPI-anchored (35). Interestingly, no ␤-1,6 glucanase genes or activity have been found, suggesting that Plb1 is linked via ␤-1,6-linked glucan to ␤-1,3-linked glucan in the central scaffold of the cell wall and that endogenous ␤-1,3 glucanases are responsible for its secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Studies by Baker et al (2) have identified three chitin deacetylases (Cda1, Cda2, and Cda3) in C. neoformans that are responsible for total chitosan production during vegetative growth. These enzymes are proteins that have been localized to the cell wall, most likely through a glycosylphosphatidylinositol anchor remnant (15). It is not known if the chitin is converted to chitosan by the chitin deacetylases while they are covalently attached to the wall or if the deacetylation occurs at an earlier step prior to the chitin deacetylases being linked to the wall.…”
Section: Discussionmentioning
confidence: 99%
“…A potential impact on secretion was also evident from the increased extracellular protease activity observed for the mfe2⌬ and mfe2⌬ had1⌬ mutants. Proteases could potentially contribute to virulence, and C. neoformans is known to secrete a variety of proteases (6,12). In general, the pleiotropic phenotypes may be due to several possible metabolic perturbations, including the accumulation of intermediates (e.g., acyl-CoA molecules), altered fatty acid availability leading to changes in phospholipid and sterol composition in membranes, and reduced acetyl-CoA production (42).…”
Section: Discussionmentioning
confidence: 99%